2016
DOI: 10.1002/2327-6924.12318
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns and organizational commitment of inpatient nurse practitioners

Abstract: Purpose Nurse practitioners (NPs) deliver a wide array of healthcare services in a variety of settings. The purpose of this study was to examine the practice patterns and organizational commitment of inpatient NPs. Methods A quantitative design was used with a convenience sample (n = 183) of NPs who attended the American Association of Nurse Practitioners (AANP) national conference. The NPs were asked to complete a demographic questionnaire, the Practice Patterns of Acute Nurse Practitioners tool and the Organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…This study also identified that research did not strongly feature in NPs work. This supports the literature which claimed that research activity in the NP role has consumed less than 4% of work time (Johnson, Brennan, Musil, & Fitzpatrick, 2016;Middleton, Gardner, Gardner, & Della, 2011). Yet, NPs are the proposed leaders in healthcare transformation (Delamaire & Lafortune, 2010;Elliott, 2017;Ford, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…This study also identified that research did not strongly feature in NPs work. This supports the literature which claimed that research activity in the NP role has consumed less than 4% of work time (Johnson, Brennan, Musil, & Fitzpatrick, 2016;Middleton, Gardner, Gardner, & Della, 2011). Yet, NPs are the proposed leaders in healthcare transformation (Delamaire & Lafortune, 2010;Elliott, 2017;Ford, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Strong organizational commitment encourages staff and makes them familiar with organizational goals and customer’s satisfaction through exhibiting better customer-oriented behaviors [ 12 ]. Organizational commitment can directly influence the quality of care and indirectly affect the healthcare organization [ 11 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition to above two constructs, commitment influences the quality of healthcare [ 11 ] and behaviors at the organizational level. Committed staff feel more satisfied with their job and endeavor to achieve organizational objectives [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the professional time use of CNSs (Darmody, , ; Kilpatrick et al, ; Leary et al, ; Mayo et al, ; Norton, Sigsworth, Heywood, & Oke, ; Oddsdóttir & Sveinsdottir, ; Ream et al, ; Wickham, ), NPs (Johnson, Brennan, Musil, & Fitzpatrick, ; Kleinpell & Goolsby, ; Martin‐Misener et al, ; Rosenfeld, McEvoy, & Glassman, ; Woo, Zhou, Lim, & Tam, ), or both (Becker, Kaplow, Muenzen, & Hartigan, ; Lincoln, ). These studies investigated the time investment of APNs using self‐reporting methods, such as diaries (Ream et al, ; Norton et al, ; Oddsdóttir & Sveinsdottir, ), instruments to register the frequency of activities (Becker et al, ; Leary et al, ; Martin‐Misener et al, ; Wickham, ), or the estimated proportion of time spent on APN roles (Darmody, ; Johnson et al, ; Kilpatrick et al, ; Kleinpell et al, ; Lincoln, ; Mayo et al, ; Rosenfeld et al, ; Wickham, ; Woo et al, ). However, recurring limitations in these studies are as follows: no random selection of the sample, unclear inclusion criteria, a lack of reasons explaining attrition, and a risk of self‐reporting bias.…”
Section: Introductionmentioning
confidence: 99%